Artificial Seawater Production for Pacific White Leg Shrimp (Litopenaeus vannamei) Culture in Closed System - Thaklaewphan, Chuthamat (Recent Science and Technology, 2025)
Concentrated brine a by-product of Thai sea salt farming can be used for raising low-salinity marine shrimp in a closed system. However, transporting and storing brine remain challenging, and its mineral composition is unstable. This research aims to study the effect of different artificial seawater treatments, flowers of salt and artificial seawater prepared from concentrated salt water on the growth of white leg shrimp (Litopenaeus vannamei) in a closed system using a completely randomized design. The experiment included three treatments: “(1) a control unit using brine (280 ppt) from a Naklua farm, (2) flower of salt obtained from the farm, and (3) artificial seawater prepared from 60 ppt. concentrated saltwater used to accelerate crystallization. Seventy-two shrimp with an initial average weight of 11.42±2.21 g were randomly placed into 200-liter fiber tanks at a density of 8 shrimp/m², with constant aeration for 60 days, while water salinity was maintained at 15 ppt. Monitoring parameters included shrimp weight, survival rate, molting frequency, and water quality. The results showed that weight gain and survival rates of shrimp across all treatments were not statistically different (p>0.05). Specifically, the survival rates for treatments 1, 2, and 3 were 98.0%, 97.3%, and 97.5%, respectively. However, FCR values in treatments 2 and 3 were lower than in treatment 1. (p<0.05) The color of boiled shrimp was compared using the Munsell Color Book, resulting in 5YR 5/12, 5YR 7/6, and 5YR 6/8 , respectively. The result from the sensory evaluation of appearance, odor, taste, and texture of shrimp showed that the three artificial seawater formulations received scores ranging from 6.47 to 6.77 (“like moderately”). Therefore, artificial seawater produced from brine and flowers of salt can be used, as the growth, survival rate, and sensory evaluation were not significantly different from those of conventional saline cultures.